Battery Characterization via Eddy-Current Imaging with Nitrogen-Vacancy Centers in Diamond - Xue Zhang; Georgios Chatzidrosos; Yinan Hu; Huijie Zheng; Arne Wickenbrock; Alexej Jerschow; Dmitry Budker (Applied Sciences, 2021)
Sensitive and accurate diagnostic technologies with magnetic sensors are of great importance for identifying and localizing defects of rechargeable solid batteries using noninvasive detection. We demonstrate a microwave-free alternating current (AC) magnetometry method with negatively charged NV centers in diamond based on a cross-relaxation feature between nitrogen-vacancy (NV) centers and individual substitutional nitrogen (P1) centers occurring at 51.2 mT. We apply the technique to non-destructively image solid-state batteries. By detecting the eddy-current-induced magnetic field of the battery, we distinguish a defect on the external electrode and identify structural anomalies within the battery body. The achieved spatial resolution is μμμ<semantics>360<mspace width="0.166667em"></mspace>μm</semantics>. The maximum magnetic field and phase shift generated by the battery at the modulation frequency of 5 kHz are estimated as 0.04 mT and 0.03 rad respectively.